Modified reporting of positive urine cultures to reduce inappropriate antibiotic treatment of catheter-associated asymptomatic bacteriuria (CA-ASB) among inpatients, a randomized controlled trial. (4th October 2021) - Pratt, Claire L.; Rehan, Zahra; Xing, Lydia; Gilbert, Laura; Fillier, Brenda; Barrett, Brendan; Daley, Peter
Abstract: Objective: To determine whether modified reporting of positive urine cultures collected from indwelling catheters improved treatment decisions without causing harm. Design: Prospective, unblinded, randomized control trial. Setting: Two tertiary-care hospitals. Participants: Overall, 100 consecutive positive urine cultures collected from catheterized inpatients were randomized between standard and modified laboratory reporting between November 2018 and June 2019. Exclusion criteria were pregnancy, current antibiotic treatment, ICU or urology admission, or neutropenia. Intervention: The modified report included significant growth without providing identification, quantification, or susceptibility. The standard report included identification, quantitation and susceptibility. Diagnosis of catheter-associated asymptomatic bacteriuria (CA-ASB) and catheter-associated urinary tract infection (CA-UTI) followed published criteria, using prospective chart review. The appropriate antibiotic treatment was defined as treatment of CA-UTI, and no treatment of CA-ASB. Patients were followed for 7 days. Results: Of 543 urine cultures, 443 (82%) were excluded. Of 100 patients, 75 (75%) had CA-ASB and 25 (25%) had CA-UTI. Treatment was given to 45 of 75 CA-ASB patients (60%) and all 25 CA-UTI patients (100%). Appropriate treatment rate was higher in the modified reporting arm than in the standard reporting arm: 57% vs 50% (+7.4%; relative risk [RR], 1.15; P = .45). Untreated CA-ASB was higher in the modified reporting arm: 45% vs 33% (+12%; RR, 1.36; P = .30). The standard report was requested for 33% of modified reports. Furthermore, 4 deaths and 26.9% adverse events occurred in the modified reporting arm, and 3 deaths and 41.3% adverse events occurred in the standard reporting arm. Conclusions: Modified reporting increased the appropriateness of treatment, and may be safe. Clinical trials identifier: ClinicalTrials.gov#NCT03488355.